THE EFFECT OF TEA PARTY STRATEGY TOWARD STUDENTS’ READING COMPREHENSION OF NARRATIVE TEXT AT GRADE X OF SMAN 12 PEKANBARU - Yulia Rilani; Mukhaiyar Mukhaiyar; Sitti Fatimah (Universitas Negeri Padang, 2018)
Teaching strategy is one of some important aspects in teaching reading process. Therefore, teacher needs some appropriate strategies to achieve the teaching reading’s goal. Tea Party is good to teach reading comprehension. This strategy helps students to comprehend the text through interactive way and discussing about limited information that they get from the text. The aim of this quasi experimental study was to investigate whether Tea Party strategy is effective than Small-Group Discussion strategy in teaching reading comprehension. The population of this study was students of the grade X of senior high school 12 Pekanbaru in 2016/2017 academic year which consist of four classes. Two classes were randomly selected as the sample of this study, namely X 2 as the experimental class and X 4 as the control class. In collecting the data, the researcher uses reading comprehension test that consisted of 40 items. The data were analyzed by using t- test. The result shows that Tea Party strategy gives better result than Small- Group Discussionin teaching reading comprehension.